1994
DOI: 10.1128/jvi.68.9.5730-5737.1994
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus infection induces transcription and secretion of transforming growth factor beta 1

Abstract: Human cytomegalovirus (CMV) infection can elicit a transitory, but profound, immunodepression in immunocompetent individuals. Cytopathogenic destruction of CMV-infected leukocytes alone does not seem sufficient to explain this phenomenon, which suggests that immune system mediators (cytokines) may play a role in amplifying local modifications wrought by CMV infection. We reported previously that transforming growth factor gi1 (TGF-f1) stimulates CMV replication (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(66 citation statements)
references
References 46 publications
(38 reference statements)
2
62
0
1
Order By: Relevance
“…87 CMV increases in vitro expression of TGF-β mRNA and protein from infected astrocytes, fibroblasts, and osteosarcoma cells. [87][88][89] Furthermore, in vitro transient expression of the CMV immediate early 1 and 2 (IE1, IE2) genes also induces TGF-β expression. 88,90 For instance, the IE2 stimulates TGF-β expression in human glioma cells, via interacting with the Egr-1 DNA-binding protein.…”
Section: Cytomegalovirusmentioning
confidence: 99%
See 1 more Smart Citation
“…87 CMV increases in vitro expression of TGF-β mRNA and protein from infected astrocytes, fibroblasts, and osteosarcoma cells. [87][88][89] Furthermore, in vitro transient expression of the CMV immediate early 1 and 2 (IE1, IE2) genes also induces TGF-β expression. 88,90 For instance, the IE2 stimulates TGF-β expression in human glioma cells, via interacting with the Egr-1 DNA-binding protein.…”
Section: Cytomegalovirusmentioning
confidence: 99%
“…[87][88][89] Furthermore, in vitro transient expression of the CMV immediate early 1 and 2 (IE1, IE2) genes also induces TGF-β expression. 88,90 For instance, the IE2 stimulates TGF-β expression in human glioma cells, via interacting with the Egr-1 DNA-binding protein. 90 Additionally, CMV also augments the FIGURE 8 A schematic illustration of the major SARS-CoV proteins and corresponding targets, by which the virus modulates the TGF-β signaling pathway FIGURE 9 A schematic illustration of the major influenza A proteins and corresponding targets, by which the virus modulates the TGF-β signaling pathway 28 -suppressed TGF-β-induced p21 expression by acting through the TGF-β-responsive element (TβRE) positioned in the p21 promoter region.…”
Section: Cytomegalovirusmentioning
confidence: 99%
“…20 Furthermore, it increases the production of transforming growth factor (TGF), which suppresses the immune system through several mechanisms, most notably the suppression of cytotoxic T lymphocyte and natural killer cells and counteracting IL-2 and tumor necrosis factor (TNF). 21 Also, different CMV proteins have been shown to suppress the apoptotic anti-viral response induced by TNF. 17,22 Recently, infection with CMV was reported to disrupt the function of the JAK-STAT signal transduction pathway as CMV rapidly decreases the level of Jak-1 by enhanced protein degradation in CMV-infected fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…This 72-kDa phosphoprotein is abundantly expressed immediately after infection (Plachter et al, 1996). In transient transfection assays, IE1 has been shown to be involved in the autoregulation of its own promoter and also in the transactivation of viral and cellular promoters, alone or in concert with other viral or cellular proteins (Stenberg and Stinski, 1985;Davis et al, 1987;Tevethia et al, 1987;Cherrington and Mocarski, 1989;Sambucetti et al, 1989;Stenberg et al, 1989;Iwamoto et al, 1990;Hagemeier et al, 1992;Monick et al, 1992;Michelson et al, 1994;Margolis et al, 1995;Yurochko et al, 1995;Kim et al, 1999;Murayama et al, 2000). It was also reported that the IE1 gene product could cooperate with another IE gene product, IE2, and adenoviral E1A to transform primary baby rat kidney (BRK) cells (Shen et al, 1997).…”
Section: Introductionmentioning
confidence: 99%